Pengaruh Persepsi Risiko, Motivasi Investasi, dan Modal Minimal Investasi terhadap Keputusan dalam Berinvestasi di Pasar Modal Syariah: (Studi Kasus pada Masyarakat Kabupaten Tulungagung) - Agustina, Riska Atika (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
The sharia capital market is all activities in the capital market that apply sharia principles in economic transaction activities and are apart from things that are prohibited by Islam, such as usury, gambling, speculation and so on. Risk perception, investment motivation, and minimum investment capital are indicators that can influence someone in investing in the Islamic capital market. The author wants to reveal how much these indicators can influence investment decisions in the Islamic capital market. This research aims to analyze and prove the influence of risk perception, investment motivation, and minimum investment capital on decisions to invest in the Islamic capital market in the people of Tulungagung Regency. The methodology used is a quantitative approach with the sampling technique used is purposive sampling where sampling is based on certain considerations such as population characteristics or previously known characteristics. The sample used was the people of Tulungagung Regency, totaling 400 respondents. The data used in this research is primary data obtained using a questionnaire. The data analysis used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, f test, t test, and coefficient of determination with the help of SPSS version 20. The results of this study show that partially risk perception has a level of significance 0.000 and tcount > ttable (11.153 > 1.966) meaning that risk perception has a significant positive effect on decisions to invest in the Islamic capital market in the people of Tulungagung Regency. Investment motivation has a significance level of 0.000 and tcount > ttable (10.629 > 1.966), meaning that investment motivation has a significant positive effect on decisions to invest in the Islamic capital market in the people of Tulungagung Regency. The minimum investment capital has a significance level of 0.000 and tcount > ttable (8.230 > 1.966), meaning that investment motivation has a significant positive effect on the decision to invest in the sharia capital market in the people of Tulungagung Regency. Meanwhile, it simultaneously has a significance level of 0.000 and fcount > ftable (136.343 > 4.459), meaning that together risk perception, investment motivation and minimum investment capital have a significant positive effect on the decision to invest in the sharia capital market among the people of Tulungagung Regency. Risk perception, investment motivation, and minimum investment capital influence investment decisions by 50.8% and 49.2% are influenced by other variables not examined in this research.